Pemilu Indonesia di Luar Negeri sebagai Arena Aktivisme Perempuan Pekerja Migran Indonesia - Susilo, Wahyu (Jurnal Perempuan, 2024)
Although since the first Indonesian general election was held in 1955, it has guaranteed political rights, especially the right to vote, for Indonesian citizens who are abroad, but in the development of policies on elections in Indonesia there has been no adequate policy update. Women Indonesian migrant workers who are the face of the majority of Indonesian citizens abroad have not participated in the implementation of Indonesian elections abroad and also have not felt the direct benefits of organising Indonesian elections abroad. This research traces the emergence of overseas election monitoring activities and political education of Indonesian migrant workers. These initiatives have encouraged the political activism of Indonesian migrant workers to ensure that Indonesian elections abroad are more qualified, responsive to the migrant worker protection agenda and encourage the representation of migrant workers in legislative political representation contested in elections